Geospatial technology approaches in urban morphology for resilient urban governance - Mohd. Noor, Norzailawati; Mohd Nor, Marina; Abdullah, Alias; Zahari, Rustam Khairi (Malaysian Institute of Planners, 2014)
This study analysed the potential of applications of geospatial technology in urban planning research in urban morphology. Urban morphology is the study of the form of human settlements and the process of their formation and transformation. It is an approach in designing urban form that considers both physical and spatial components of the urban structure. This study was conducted in Georgetown, Penang with the main purpose to identify the evolution of urban morphology and the land use expansion using remote sensing images and Geographical Information System (GIS) technique. Four series of temporal satellite SPOT 5 J from 2004, 2007, 2009, and 2014 were used to detect an expansion of land use development using change detection technique. Three types of land use were identified, namely built-up area, unbuilt-up area, and water bodies with a good accuracy of above 85%. The result showed that the built-up area significantly increased due to the rapid development in urban area. Finally, the result provided an understanding and strengthened the relationship between urban planning and geospatial applications in creating sustainable and resilient city and future urban governance.